Annual Survey of Statistical Information: The Branches of National Spending - Marschak, Jakob (Econometrica, 1933)
THE econometric approach to statistics is a rather ambitious one. The econometrician is not content with mere description and historical or geographical comparison of economic data. He aims at obtaining invariant features of economic phenomena, invariant, at least, as long as the main institutional conditions of a given economic order do not substantially vary. He considers economic invariants as an aim worthy of scientific endeavor, even if they prove to be confined to some very general characteristics common to a loose family of curves. Of course, the numerical formulation of such is in itself again nothing more than a description of facts. But in the econometric approach an endeavor is made to reduce these facts to rules which can stand the test of applicability to, or of forecasting of, other facts. Among recent statistical works having immediate econometric interest, three more important groups may be discerned: (1) attempts towards a construction of demand and supply curves of certain commodities (including productive factors), (2) analysis of business cycles, and (3) numerical investigation into the branches of national spending, including saving or investment, and production (possibly connected with research into national stocks and cash), and into time changes in their proportions. Obviously, the three subjects are closely connected with one another. The proportions between the main economic currents depend on price ratios between commodities and/or productive factors; and the analysis of business cycles, if it is more than an enumeration of symptoms, is hardly possible without knowledge of the reactions to which the different commodities and productive factorsand consequently the different streams of production and spendingare likely to be originated by given changes of the circumstances. The three groups of research have, however, some differences in the technical apparatus employed, and these permit a separate review. We are concerned, in this review, with the third group only. On questions recently discussed in economic theory, such as the influence of profits or of capital accumulation on national productivity, some light may be thrown if we know the order of magnitude of the parameters concerned, and the intensity and velocity of their mutual reactions.